Microfinance and Household Welfare : Cambodia Policy Note - Pimhidzai, Obert; Tong, Kimsun; Anantavrasilpa, Ratchada; Popovic, Andrej; Mel, Sokim; Sanchez Martin, Miguel Eduardo (World Bank, Washington, DC, 2019)
Cambodia's openness to trade and financial flows has fueled one of the fastest credit growth episodes in Asia.A remarkable expansion in formal microfinance lenders contributed to increased access to credit. Since the promulgation of the National Strategy for Microfinance in 2007, Cambodia’s microfinance sector has expanded rapidly, with both assets and credit growing at annualized rates of over 40 percent. While access to credit has helped ease financial constraints for households, one key concern is how the cost of credit and increased exposure to risk might affect household welfare. At the household level, low financial literacy could result in poor borrowing decisions and heighten risks. There are concerns that households may be over-borrowing and increasing their exposure to risks, as there are signs that the market is already highly saturated, given estimated absorption capacity at this level of development. This policy note assesses the impact of access to credit on household welfare in Cambodia and providesevidence on the drivers of the cost of credit in the microfinances sector. To fill the existing knowledge gaps, this policy note uses the latest available data from official sources to provide evidence on (i) the impact of microcredit on household welfare, (ii) profitability and cost of credit in the microfinance sector, and (iii) the effects of the interest rate cap in the sector. This note ultimately presents a series of policy options aimed at facilitating affordability and reducing the cost of credit, while maintaining sector profitability and minimizing risks (both for households and the financial system). The policy options have been developed in consultation with sector stakeholders.